Tourism damand analysis: determining complementary destinations for collaborative agreements between ASEAN countries - Pang, Looi Fai; Lee, Chin (2012)
Various strategic directions have been proposed under the ASEAN Tourism Strategic Plan (ASTP) 2011-2015 to promote regional collaboration in tourism. A key initiative is encouraging regional travel.However ease of travel has its dangers in that it promotes competition among ASEAN member states for tourists. Collaboration and strategic alliances would prevent duplications of attractions allowing countries to focus on their core competencies. This study seeks to identify the main tourist demand determinants and the substitutability of neighbouring destinations. This will provide information for the establishment of collaborative agreements for complementary destinations and the development of competitive strategies for substitute destinations within a region. Panel data regression was used to investigate the explanatory variables of tourism demand of Malaysia and to identify the substitutability of its immediate neighbours Indonesia, Singapore and Thailand. The findings indicate that Singapore is a substitute destination whereas Indonesia and Thailand are complementary destinations suggesting the need to develop tourism cooperatively with Singapore to prevent unhealthy competition.